2023
DOI: 10.1164/rccm.202210-1881oc
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Expression Is Lower in Current Smokers at both Transcriptomic and Protein Levels

Alen Faiz,
Rashad M. Mahbub,
Fia Sabrina Boedijono
et al.

Abstract: Rationale IL-33 is a proinflammatory cytokine thought to play a role in the pathogenesis of asthma and chronic obstructive pulmonary disease (COPD). A recent clinical trial using an anti–IL-33 antibody showed a reduction in exacerbation and improved lung function in ex-smokers but not current smokers with COPD. Objectives This study aimed to understand the effects of smoking status on IL-33. Methods We investigated the association of smoking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Single-level transcriptomics and proteomics analyses have been used to unravel the complexity of chronic obstructive pulmonary disease (COPD) pathogenesis and treatment response ( 1 4 ). Thus far, resected lung tissue or bronchial biopsies and brushes have been considered to be the most relevant samples to investigate.…”
mentioning
confidence: 99%
“…Single-level transcriptomics and proteomics analyses have been used to unravel the complexity of chronic obstructive pulmonary disease (COPD) pathogenesis and treatment response ( 1 4 ). Thus far, resected lung tissue or bronchial biopsies and brushes have been considered to be the most relevant samples to investigate.…”
mentioning
confidence: 99%
“…In this issue of the Journal , to examine potential mechanisms that may underlie these clinical findings, Faiz and colleagues (pp. 1075–1087 ) explored the expression of the IL-33 pathway in relation to smoking status in several datasets of transcriptomic analysis of lung airways ( 10 ). In bulk transcriptome studies, they found that mRNA levels of IL-33 were reduced in current smokers when compared with ex- (or never-)smokers.…”
mentioning
confidence: 99%